Cannabinoid CB1 Receptor Expression and Localization in the Dorsal Horn of Male and Female Rat and Human Spinal Cord - Jessica Parnell; Newton Martin; Annemarie Dedek; Christopher Rudyk; Jeffrey Landrigan; Justin Bellavance; Simon VanDerLoo; Eve C. Tsai; Michael E. Hildebrand (Taylor & Francis Group, 2023)
ABSTRACTBackground Preclinical and clinical evidence suggests that cannabis has potential analgesic properties. However, cannabinoid receptor expression and localization within spinal cord pain processing circuits remain to be characterized across sex and species.Aims We aimed to investigate the differential expression of the cannabinoid type 1 (CB1) receptor across dorsal horn laminae and cell populations in male and female adult rats and humans.Methods To investigate and quantify CB1 receptor expression in the spinal dorsal horn across species, we refined immunohistochemical procedures for successful rat and human fixed tissue staining and confocal imaging. Immunohistochemical results were complemented with analysis of CB1 gene (CNR1) expression within rodent and human dorsal horn using single-cell/nuclei RNA sequencing data sets.Results We found that CB1 was preferentially localized to the neuropil within the superficial dorsal horn of both rats and humans, with CB1 somatic staining across dorsal horn laminae. CB1 receptor immunoreactivity was significantly higher in the superficial dorsal horn compared to the deeper dorsal horn laminae for both rats and humans, which was conserved across sex. Interestingly, we found that CB1 immunoreactivity was not primarily localized to peptidergic afferents in rats and humans and that CNR1 (CB1) but not CNR2 (CB2) was robustly expressed in dorsal horn neuron subpopulations of both rodents and humans.Conclusions The conserved preferential expression of CB1 receptors in the superficial dorsal horn in male and female rodents and humans has significant implications for understanding the roles of this cannabinoid receptor in spinal mechanisms of nociception and analgesia.